Survey and Monitoring of Citrus Greening Disease and its Vector, Asian Citrus Psyllid (Diaphorina citri Kuwayama) in Sweet Orange Orchards of Sindhuli, Nepal - Neupane, Abhishek; Shrestha, Aaradhana; Acharya, Prajwal; Adhikari, Debraj (Journal of the Plant Protection Society, 2024)
This study was conducted to evaluate farmers’ perceptions of citrus greening disease or Huanglongbing (HLB) and its vector, Diaphorina citri Kuwayama (Asian Citrus Psyllid (ACP)) in the major sweet orange growing regions of Sindhuli in 2022. The study consisted of two major parts, farmer’s survey of HLB and monitoring of the vector. As the study revealed, 73.77% of the orchards exhibited symptoms indicative of citrus greening disease, 83.3% of the farmers were found to be aware of the disease, and 66.67% were aware of the symptoms it produced; however, only 43.14% of farmers were aware of the vector. Cutting off the diseased tree (priority index(I) = 0.63) was the most followed strategy after the incidence of the disease. The use of chemical pesticides (I = 0.85) was ranked first among the strategies being applied to control the vector. The total ACP count was found to be the highest in July (x̄ = 33.2). Its appearance in the orchard became evident after the end of winter (March), and gradually increased its population in spring (April-May), attained maximum population in the rainy season (June-July), and started declining again in fall (August).